2020
DOI: 10.3390/ijerph17010354
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vibration Rolling with and without Dynamic Muscle Contraction on Ankle Range of Motion, Proprioception, Muscle Strength and Agility in Young Adults: A Crossover Study

Abstract: Vibration rolling (VR) has emerged as a self-myofascial release (SMR) tool to aid exercise performance when warming up. However, the benefits of VR on exercise performance when combined with dynamic muscle contraction are unclear. The purpose of this study was to investigate the immediate effects of the combination of VR with dynamic muscle contraction (DVR), VR, and static stretching (SS) during warm-up on range of motion (ROM), proprioception, muscle strength of the ankle, and agility in young adults. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 40 publications
1
22
4
1
Order By: Relevance
“…Along with specific muscle strength, adequate ankle ROM allows for efficient force generation and ankle strategy execution during balance disturbance [ 23 ]. Contrary to those studies that found significant and positive training effects in plantar flexion and dorsiflexion [ 34 ], the present study only showed significant improvements in plantar flexion. Moreover, there was a significant reduction in the ROM of the right dorsiflexion.…”
Section: Discussioncontrasting
confidence: 99%
“…Along with specific muscle strength, adequate ankle ROM allows for efficient force generation and ankle strategy execution during balance disturbance [ 23 ]. Contrary to those studies that found significant and positive training effects in plantar flexion and dorsiflexion [ 34 ], the present study only showed significant improvements in plantar flexion. Moreover, there was a significant reduction in the ROM of the right dorsiflexion.…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, the amount of angle change for dorsi exion ROM was greatly improved after VR. These results are supported by those of previous studies in which VR increased ankle ROM [22,24]. This effective result is thought to be the result of vibration stimulation leading to an increase in blood ow and temperature, which could provoke ROM improvements [25].…”
Section: Discussionsupporting
confidence: 88%
“…Participants positioned the vibrating foam roller below the gastrocnemius of their paretic side leg. The frequency of VR was 28 Hz, which has been used in many prior studies [13,22]. Thereafter, patients performed 60 s of dorsi exion and plantar exion of their ankle (Fig.…”
Section: Exercise Protocols Vrmentioning
confidence: 99%
“…The choice to use vibratory stimulation in dysfunctional patients was based on evidence from previous studies showing the effectiveness of local vibration therapy in reducing chronic musculoskeletal pain and in delaying the onset of muscular pain [ 10 , 11 ]. Several studies have shown that vibratory stimulus is capable of exciting afferents in both the Pacinian corpuscles and in the receptors of the skin, periodontium, muscle spindles, and tendon organs [ 15 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This therapy is most frequently applied in the treatment of chronic pathologies affecting the muscles, tendons, and joints. Several studies evaluating the impact of local vibration therapy on skeletal muscles and joints have highlighted its effectiveness for increasing joint mobility and decreasing pain [ 10 , 11 ], but analysis of its potential for the temporomandibular region is still lacking. Only two studies have addressed the application of this therapy to TMD and both demonstrate its effectiveness for muscle pain relief [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%